Comprehensive Mechanism Analysis of Mesoporous‐Silica‐Nanoparticle‐Induced Cancer Immunotherapy. Issue 10 (14th March 2016) - Wang, Xiupeng; Li, Xia; Yoshiyuki, Kazuko; Watanabe, Yohei; Sogo, Yu; Ohno, Tadao; Tsuji, Noriko M.; Ito, Atsuo
Abstract : A plain mesoporous silica nanoparticle without any immunomodulatory molecules significantly enhances anticancer immunity in vivo. Comprehensive mechanism of mesoporous‐silica‐nanoparticle‐induced cancer immunotherapy is analyzed in this paper. The mesoporous silica nanoparticle promotes both Th1 and Th2 immune responses, as it accelerates lymphocytes proliferation, stimulates IFN‐γ, IL‐2, IL‐4, and IL‐10 cytokine secretion by lymphocytes ex vivo, and increases IgG, IgG1, IgG2a, IgM, and IgA antibody titers in mice serum compared with those of alum and adjuvant‐free groups. Moreover, the mesoporous silica nanoparticle enhances effector memory CD4 + and CD8 + T cell populations in three most important immune organs (bone marrow, lymph node, and spleen) of mice compared with those of alum and adjuvant‐free groups three months after adjuvant injection. The present study paves the way for the application of mesoporous silica nanoparticle as immunoadjuvant for cancer immunotherapy. Abstract : A plain mesoporous silica (MS) nanoparticle without any immunomodulatory molecules enhances anticancer immunity in vivo. The plain MS nanoparticle promotes both Th1 and Th2 immune responses, enhances the effector memory CD4 + and CD8 + T cell populations in three most important immune organs (bone marrow, lymph node, and spleen).